Plastid Nucleoids: Insights into Their Shape and Dynamics - Nishimura, Yoshiki (Plant and cell physiology, 2024)
Abstract Chloroplasts/plastids are unique organelles found in plant cells and some algae and are responsible for performing essential functions such as photosynthesis. The plastid genome, consisting of circular and linear DNA molecules, is packaged and organized into specialized structures called nucleoids. The composition and dynamics of these nucleoids have been the subject of intense research, as they are critical for proper plastid functions and development. In this mini-review, recent advances in understanding the organization and regulation of plastid nucleoids are overviewed, with a focus on the various proteins and factors that regulate the shape and dynamics of nucleoids, including DNA-binding proteins and membrane anchorage proteins. The dynamic nature of nucleoid organization, which is influenced by a variety of developmental cues and the cell cycle, is also examined.